RELATIVE COMPETITIVENESS OF SOYBEAN IN SIMULTANEOUS GROWTH WITH ALEXANDERGRASS (Brachiaria plantaginea) - AGOSTINETTO, Dirceu; RIGOLI, Rubia Piesanti; GALON, Leandro; MORAES, Pedro Valério Dutra de; FONTANA, Lisiane Camponogara (Scientia Agraria, 2009)
The ability of a certain plant to compete with another one is related to factors such as species, population, emergence period and morphophysiologic characteristics. Experiments in substitution series allow the study of population effects and proportion of plants in species association, the importance of intra and interspecific competition and the ecological niche differentiation. The objective of this study was to investigate the competitive ability of soybean plants with the weed plant alexandergrass through the experimental method of substitution series. The experiment was carried out with a total population of 200 plants m-2 and proportions of 100:0, 75:25, 50:50 and 0:100 for soybean and alexandergrass, respectively, in a completely randomized design, with four replications. Competitive analysis was performed through diagrams applied to substitutive experiments and morphologic variables. Deviations observed in relative productivity lines and total relative production, in relation to expected linear lines, for both species, resulted in concave lines and smaller than 1, demonstrating antagonism in the growth of species in association. For soybean and alexandergrass, intraspecific competition was more important than interspecific competition.